Overexpression of a small GTP‐binding protein Ran1 in Arabidopsis leads to promoted elongation growth and enhanced disease resistance against P. syringae DC3000. (28th October 2021) - Xu, Peipei; Ma, Wei; Liu, Jing; Hu, Jinbo; Cai, Weiming
SUMMARY: Plants resist infection through an innate immune response, which is usually associated with slowing of growth. The molecular mechanisms underlying the trade‐off between plant growth and defense remain unclear. The present study reveals that growth/defense trade‐offs mediated by gibberellin (GA) and salicylic acid (SA) signaling pathways are uncoupled during constitutive overexpression of transgenic AtRAN1 and AtRAN1Q72L (active, GTP‐locked form) Arabidopsis plants. It is well known that the small GTP‐binding protein Ran (a Ras‐related nuclear protein) functions in the nucleus–cytoplasmic transport of proteins. Although there is considerable evidence indicating that nuclear–cytoplasmic partitioning of specific proteins can participate in hormone signaling, the role of Ran‐dependent nuclear transport in hormone signaling is not yet fully understood. In this report, we used a combination of genetic and molecular methods to reveal whether AtRAN1 is involved in both GA and SA signaling pathways. Constitutively overexpressed AtRAN1 promoted both elongation growth and the disease resistance response, whereas overexpression of AtRAN1Q72L in the atran2atran3 double mutant background clearly inhibited elongation growth and the defense response. Furthermore, we found that AtRAN1 coordinated plant growth and defense by promoting the stability of the DELLA protein RGA in the nucleus and by modulating NPR1 nuclear localization. Interestingly, genetically modified rice ( Oryza sativa ) overexpressing AtRAN1 exhibited increased plant height and yield per plant. Altogether, the ability to achieve growth/defense trade‐offs through AtRAN1 overexpression provides an approach to maximizing crop yield to meet rising global food demands. Significance Statement: A common explanation for the 'plant growth or defense dilemma' is that high expression of defense‐related factors requires metabolic resources at the expense of growth. In the current study, we demonstrate that AtRAN1 overexpression stimulates GA signaling by promoting DELLA protein degradation in the nucleus and increases SA signaling by promoting NPR1 nuclear localization. Unlocking the ability to modulate the growth/defense trade‐off through nucleo‐ cytoplasmic trafficking and signaling processes may provide an approach to generating plants with traits that have practical applications.